Experimental Design and Analysis in Animal Sciences - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
T R Morris (Department of Agriculture, University of Reading, UK). CABI. 1999. 240 pp.ISBN 0 85199 349 4.£22.50 $40.00 Euro 38.50(See earlier CABI reference for address)